Konflik Rusia-Ukraina (Sejarah, Resolusi, serta Manajemen Konflik) - Adipa Parawita; Era Yura; Endang Andrian; Fajar Adilah Pratama; Nasar Nasar; Yusawinur Barella (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2025)
The ongoing Russia-Ukraine conflict has become one of the most complex issues in global geopolitics, with far-reaching impacts on world security, economy and stability. This research aims to analyze the root causes of conflict, resolution efforts that have been made, as well as the effectiveness of conflict management based on historical and academic approaches. This research uses a qualitative method with a literature study approach to explore information from various credible sources. The research results show that this conflict was triggered by the long history of relations between the two countries, especially since the collapse of the Soviet Union, followed by the annexation of Crimea in 2014 and military invasion in 2022. Even though various diplomatic efforts and economic sanctions have been implemented, tensions still continue due to the incompatibility of geopolitical interests between Russia and Western countries. This study highlights the need for a multilateral approach based on international mediation to create sustainable peace. It is hoped that this article can contribute to academic understanding regarding international conflicts and strategies for resolving them.